ANALISIS STRATEGI GURU DALAM MENGELOLA PERILAKU TANTRUM PADA ANAK USIA DINI DI TK KRISTEN “BAIK” PAPUA - Ludia Napan; Varia Virdania Virdaus (MOTORIC, 2026)
This study aims to describe the forms of tantrums that occur in early childhood and analyze teacher strategies in managing tantrum behavior in the "Baik" Christian Kindergarten in Papua. Tantrums in early childhood are a form of emotional outburst that can appear through loud crying, screaming, throwing objects, refusing to be touched, or rolling on the floor when the child is not yet able to manage his feelings appropriately. This study used a descriptive qualitative approach. The subjects were teachers of the "Baik" Christian Kindergarten who directly interact with early childhood and have experience in handling tantrums in the classroom. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results showed that children's tantrums generally occur when children feel frustrated, their toys are taken, their work is disturbed, or they are not yet able to understand the concept of sharing. Teacher strategies in managing tantrum behavior are carried out through empathetic, preventive, corrective, and reflective approaches. The empathetic approach is carried out by approaching the child slowly, providing gentle touch, hugs, and using positive words. The preventive approach is carried out by creating a comfortable classroom atmosphere, providing directions before activities, and establishing routines that make children feel safe. The corrective approach involves gently setting boundaries, while the reflective approach is implemented after the child has calmed down through simple dialogue about their feelings. Research findings also indicate that the values ??of love, patience, closeness to Papuan culture, and Christian values ??support teachers' strategies in creating a safe and conducive learning environment for children's social-emotional development. Keywords: teacher strategies, tantrums, early childhood, emotional regulation, ECE